CLINICAL SIGNIFICANCE OF INFILTRATIVE GROWTH IN BREAST CANCER TUMORS - Lola T. Alimkhodzhaeva; Sherzod I. Ruziyev; Orifa M. Ahmadjanova (Central Asian Journal of Medicine, 2025)
Even though breast cancer is currently one of the most studied oncological pathologies, the question of the occurrence, characteristics, and prevalence of infiltrating breast cancer remains unclear, as evidenced by the wide dispersion of figures on the frequency of this disease according to various authors - from 2 to 62%. To date, issues related to the diagnosis, selection of adequate treatment, and prediction of the outcome of the disease in infiltrating breast cancer remain particularly complex, considering that in most published studies, a limited number of markers do not allow for full clarification of the biological profile of this type, there is no data on the prognostic significance, and a comprehensive diagnostic algorithm combining morphological and IGC criteria has not been defined.